Experimental Study on Fatigue Performance of Composite Box Girder With Steel Bottom Plate and Corrugated Steel Webs - Shijin Wang; Genhui Wang; Jiang Fan; Zichen Zhang (Advances in Civil Engineering, 2024)
In order to study the fatigue performance and fatigue failure mode of the composite box girder with steel bottom plate and corrugated webs (SBCSWs), the model beam was made and the constant and variable amplitude fatigue experiment were performed. Combined with ABAQUS finite element software, the strain, deflection, and fatigue failure mode of the composite box girder with SBCSWs were analyzed. The results showed that the slope of the load–deflection curve, the slope of the load–strain curve, and the neutral axis height of the model beam did not change during the constant amplitude fatigue test. In the variable amplitude fatigue test, as the fatigue loading time and fatigue load amplitude increased, the slope of the load–deflection curve and the slope of the load–strain curve of the model beam decreased significantly, while the neutral axis height increased significantly. The section strain of the composite box girder with SBCSWs was consistent with the quasi-plane section assumption. The fatigue failure of the composite box girder with SBCSWs began at the stress concentration at the junction of the steel bottom plate and the corrugated webs. The fatigue fracture section has typical fatigue fracture characteristics.